Reprimarization in the periphery? The brazilian case (2003-2013) - Orozco, Christian (Papeles de Europa, 2016)
The purpose of this research is to get into the discussion about the meaning of deindustrialization, understanding that this phenomenon can manifest itself in different ways depending on two factors: the first related to the level of general and industrial development in an economy; and second, associated with the abundance / dependence on one or a small basket of commodities. Moreover, assuming that the Brazilian economy has been undergoing a process of dependent industrialization since the late eighties and, above all, the mid-nineties; we focus on finding if in the period between 2003 and 2013 there has been a process of reprimarization, interpreting this phenomenon as a branch of the so-called Dutch disease. The empirical methodology is based on analysis of data organized in tables and figures. The main conclusion, anticipated here, is that there is little evidence that Brazil has experienced during the period of study a process of reprimarization of its productive structure.